Diversion of nuclear, biological, and chemical weapons expertise from the Former Soviet Union : understanding an evolving problem - Parachini, John.; Mosher, David E.; Baker, John C., 1949-; Chase, Michael S.; Daugherty, Michael; Rand eBooks (Santa Monica, CA : RAND, 2005)
Since the early 1990s, the United States has been concerned about the diversion of expertise and sensitive information from the nuclear, biological, and chemical (NBC) weapons complexes of the former Soviet Union (FSU). This documented briefing offers an assessment of the threat of diversion from the FSU and examines each of its key components, including the nation-states and individuals who seek to illicitly acquire NBC weapons expertise and the institutions and individuals who already have it. The authors argue that the threat goes beyond just scientists to highly skilled technicians, retirees, and key administrative and support personnel who can provide sensitive information. The authors further argue that applying a simple supply-and-demand model to the problem of proliferation overlooks the critical role that various barriers and disincentives to proliferation have played in keeping the actual number of cases of diversion low.
Introduction and Analytical Approach -- Supply of Proliferation-Critical Knowledge -- Demand for Proliferation-Critical Knowledge -- Barriers to Knowledge Transfer -- Key Findings and Policy Implications.
"RAND National Security Research Division."
Includes bibliographical references (p. 45-58).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Biological weapons -- Former Soviet republics; Chemical weapons -- Former Soviet republics; Deterrence (Strategy); Nuclear arms control; Nuclear nonproliferation -- Former Soviet republics; Nuclear weapons -- Former Soviet republics; Electronic books